Pengaruh Kinerja Guru Bidang Studi terhadap Prestasi Belajar Siswa Kelas X SMK Bisnis dan Teknologi Bekasi - Bakti Toni Endaryono; Tjipto Djuhartono (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The purpose of this study is to discuss and analyze the performance of subject teachers influencing students’ learning outcomes in SMK Business and Technology Bekasi. The method used in this research is quantitative methods, data collection techniques through interviews, observation and documentation; data analysis techniques in this study using simple regression analysis and coefficient of determination. This research was conducted for 6 months starting from September 2020 to February 2021 with four stages, namely planning, implementing, processing data and reporting research results, while the results of this study were that the performance of teachers in the field of study had an effect on student achievement by 6.69%, with the calculation of the simple correlation coefficient of 0.69% while the result of the coefficient of determination of 47.61% means 52.39% is influenced by other factors not mentioned in this study.